Community Solar: How to Make it Shine - Johnson, Bruce. (Tufts University. Tisch Library., 2019)
The major focus of this thesis was to identify and analyze different state level policies that have a major influence on the implementation of Community Solar (CS). CS is classified as both a distributed-generation and renewable energy source. It is rapidly growing, while expanding the ability for a variety of different consumers and firms to participate in the solar energy economy. Through a literature review, this thesis began by identifying a wide range of policies that can enable and influence CS implementation, ranging from nearly essential factors like having energy credit valuation systems, to providing tax benefits. Through this research, I developed a state level policy scoring system, taking into account 17 different policy related factors. This scoring system was applied to California, Colorado, Massachusetts, Minnesota, and New York, the five states that currently have the most installed CS. This was done by developing an inventory of what policies each state has, and assigning a policy score based on their policies. Next, the total CS implementation for each of these states was inventoried, and was also normalized to take into account total state solar potential and population. Based on these scores and implementation, two linear regression models were run showing a positive relationship between having a high policy score and having high levels of CS implementation. Additionally, a correlation matrix was run to identify which individual policy factors have a more direct significant effect on implementation. Limited by the small sample size, little statistical significance was found in the correlation matrix. However, there was a significant positive relationship between tax related factors, including income tax deduction and grants and rebates, and implementation. This thesis serves as a strong baseline and roadmap for CS policy analysis, and should be replicated and expanded upon in the future as CS implementation continues to increase and more data becomes available.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Justin Hollander, and Ann Rappaport.; Keywords: Urban planning, and Environmental studies.